2021
DOI: 10.1002/ente.202000945
|View full text |Cite
|
Sign up to set email alerts
|

Molten‐Salt Technology Application for the Synthesis of Photocatalytic Materials

Abstract: Most of the photocatalytic materials are prepared by wet chemical methods and calcination methods. These preparation methods usually have the problems of slow reaction speed and low crystallinity of products, which seriously restrict the development of photocatalytic technology. Molten salt method (MSM) has attracted much attention of researchers because of its unique advantages in optimizing the synthesis route of photocatalyst. Herein, the application of molten salt technology in the preparation of photocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 95 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…Based on Figure 4, the particle sizes were decreasing but they agglomerated. It indicates that Fe doping in uences the growth of CTO grain particles (Huang et al, 2016;Luo et al, 2021). Sato et al (2019) reported that the substitution of Ti 4+ with Fe 3+ with a smaller charge caused an unbalance charge, thus compensated by the reveal of oxygen vacancy.…”
Section: Resultsmentioning
confidence: 99%
“…Based on Figure 4, the particle sizes were decreasing but they agglomerated. It indicates that Fe doping in uences the growth of CTO grain particles (Huang et al, 2016;Luo et al, 2021). Sato et al (2019) reported that the substitution of Ti 4+ with Fe 3+ with a smaller charge caused an unbalance charge, thus compensated by the reveal of oxygen vacancy.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, researchers have developed a new type of carbon nitrides with poly heptazine imide (PHI) structure, which are highly stable and crystalline. PHIs are generally synthesized from nitrogen-rich compounds through solid-state reactions with alkali metal chlorides or thermal condensation of CN precursors in eutectic salt melts [ 61 , 62 ]. Post-modification is another way to prepare PHI-based CNs by treating the condensed CNs with alkali metal salts.…”
Section: Types and The Characteristics Of Carbon Nitridesmentioning
confidence: 99%
“…Furthermore, it is also important to choose the appropriate doping method. The molten-salt method of element doping is an efficient and low-cost method because its molten-salt liquid environment can make the element distribution more uniform, and the treatment process before and after the reaction is very simple [ 28 ].…”
Section: Introductionmentioning
confidence: 99%